Utilisation des sécrétions de myriapodes chez les lémurs et les sapajous : fonction curative ou signalisation sociale ? - Bruno Simmen; Laurent Tarnaud (Revue de Primatologie)
Body-rubbing with millipedes is repeatedly documented in primates living under natural conditions, mainly in capuchin monkeys (Cebus spp.). Various functional (zoopharmacognosy, ingestion, social) and non-functional hypotheses (sensory, auto stimulation) have been proposed to explain this behaviour based on the distinctive typology and context in which it occurs. We present here qualitative observations of non-feeding use of millipedes in a comparative perspective in two primate species. Opportunistic data were collected in a prosimian species (a hybrid form of Eulemur sp.) in a gallery forest South of Madagascar (occurrences in January 2005) and in capuchin monkeys (Cebus apella) in a tropical rainforest in French Guyana (occurrences in March-April 1996). Whereas capuchin monkeys anoint large parts of their fur with millipede secretions, lemurs only rub the circum-genital area, usually after smelling the millipedes, which appears to trigger a stereotyped response analogous to flehmen. Handling the millipedes in itself does not automatically result in millipedes secreting benzoquinones so that when lemurs and capuchin monkeys bite the arthropods (eventually blowing the legs off), they increase the probability of repulsive liquid being oozed. Associative learning of the handling conditions required to trigger millipedes’ secretions appears very efficient given the rare and opportunistic use of these arthropods by both primate species. We suggest that millipede use in our study is either a marginal form of social communication by which the individual odour is reinforced by anointment with strong smelling odours (Eulemur in which olfaction and scent marking are of paramount importance to social relationships) or, in agreement with self-protection hypotheses, a behaviour that contribute to eliminate or protect from external parasites (Cebus).